The subjection and spectacle of social work: deconstructing and reckoning with social work’s power of policing - Rangel, Michael (Social work, white supremacy, and racial justice, 2023)
Social work has been an integral part of the carceral state in utilizing power, control, and discipline in service to others. The societal problems social work so diligently works to end persist, because there has been no investigation to interrogate and transform the field from within. Recently, social workers have been prompted to collaborate with—or even replace—police, but social workers’ engagement in punitive and disciplinary practices has only deepened the relationship between the two. This chapter argues that American professional social work has complicitly created, sustained, and expanded the carceral state. Incorporating critical theory, cultural studies, and feminist methodologies, this chapter promotes an engagement beyond current understanding of knowledge production and philosophies of care, sociality, and carcerality. Social work must build, imagine, and actualize the abolishment of the carceral state to then root the profession in a fabrication of an entirely different social work/ing.